Fungemia associated with Schizophyllum commune in Brazil - Oliveira, Manoel Marques Evangelista (2017)
Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Laboratório de Micologia. Rio de Janeiro, RJ. Brasil.